Development of nonlinear framework for simulation of Typhoon-induced buffeting response of Long-span bridges using Volterra series. (1st October 2021) - Ali, Khawaja; Katsuchi, Hiroshi; Yamada, Hitoshi
Highlights: Extension of LU model to Volterra model improves the buffeting analysis results. Nonlinearity and non-stationary wind effects are critical to the bridge response. Non-stationary wind effects can be characterized by the time-varying mean wind. Time-varying mean wind speed causes the time-varying mean response of the bridge. Aerodynamic nonlinearity effects may become significant at high wind speeds. Abstract: This paper presents a nonlinear time-domain analysis framework to simulate the buffeting response of long-span bridges subjected to the typhoon winds. The analysis framework separates the aerodynamic forces generated on the bridge deck into low- and high-frequency components modelled by the quasi-steady and Volterra series-based wind load models, respectively. The aerodynamic nonlinearity and non-stationary wind effects existing in the wind-bridge interaction are incorporated in the analysis framework in terms of the ① static force coefficients measured at low-frequency effective angle of attack, ② flutter derivatives identified at varying angles of attack, ③ higher order fluid memory terms of the Volterra series and ④ time-varying mean wind speed. The efficacy of the proposed framework is verified by presenting the numerical example of a suspension bridge fully immersed in the typhoon winds with aerodynamic characteristics sensitive to the effective angle of attack. The dynamic analysis results show good agreement in the simulation of the typhoon-induced buffeting response of the bridge deck. Moreover, the simulation results are also compared with the measurements, and the existing linear and nonlinear wind load models to elucidate the efficiency of the proposed framework.